The Influence of Interactive Slide Design on Cognitive Load in Biology Learning: A Bibliometric Analysis - Fitriani Laili Nur; Rizhal Hendi Ristanto; Tri Handayani (Universitas Negeri Semarang, 2026)
Biology learning often involves complex and abstract information that can increase students’ cognitive load and affect learning effectiveness. Therefore, cognitive load has become an important topic in science education research. This study aims to analyze the development and research trends related to cognitive load in biology learning using a bibliometric approach. Data were collected from the Scopus database, focusing on journal articles and review papers published between 2014 and 2024. A total of 200 documents were analyzed using Biblioshiny. The analysis included co-occurrence, co-authorship, citation, and thematic mapping techniques. The results show an increasing trend in publications, indicating growing attention to cognitive load in biology learning. The findings also reveal that research in this field is interdisciplinary and has shifted from basic cognitive studies toward more applied approaches, particularly in instructional design and learning media. Key authors, journals, and highly cited documents play an important role in shaping research development. Overall, this study provides an overview of research trends and highlights opportunities for future studies in developing effective learning strategies based on cognitive load principles.